A phase 1 open‐label trial evaluating focused ultrasound unilateral anterior thalamotomy for focal onset epilepsy. Issue 4 (1st March 2023) - Krishna, Vibhor; Mindel, Jesse; Sammartino, Francesco; Block, Cady; Dwivedi, Alok Kumar; Van Gompel, Jamie J.; Fountain, Nathan; Fisher, Robert
Abstract: Objective: Focused ultrasound ablation (FUSA) is an emerging treatment for neurological and psychiatric diseases. We describe the initial experience from a pilot, open‐label, single‐center clinical trial of unilateral anterior nucleus of the thalamus (ANT) FUSA in patients with treatment‐refractory epilepsy. Methods: Two adult subjects with treatment‐refractory, focal onset epilepsy were recruited. The subjects received ANT FUSA using the Exablate Neuro (Insightec) system. We determined the safety and feasibility (primary outcomes), and changes in seizure frequency (secondary outcome) at 3, 6, and 12 months. Safety was assessed by the absence of side effects, that is, new onset neurological deficits or performance deterioration on neuropsychological testing. Feasibility was defined as the ability to create a lesion within the anterior nucleus. The monthly seizure frequency was compared between baseline and postthalamotomy. Results: The patients tolerated the procedure well, without neurological deficits or serious adverse events. One patient experienced a decline in verbal fluency, attention/working memory, and immediate verbal memory. Seizure frequency reduced significantly in both patients; one patient was seizure‐free at 12 months, and in the second patient, the frequency reduced from 90–100 seizures per month to 3–6 seizures per month. Significance: This is the first known clinical trial to assess the safety, feasibility, and preliminary efficacy of ANT FUSA in adult patients with treatment‐refractory focal onset epilepsy.